2021
DOI: 10.1111/jcmm.16403
|View full text |Cite
|
Sign up to set email alerts
|

Priming of mesenchymal stem cells with a hydrosoluble form of curcumin allows keeping their mesenchymal properties for cell‐based therapy development

Abstract: Mesenchymal stem cells are increasingly studied for their use as drug‐carrier in addition to their intrinsic potential for regenerative medicine. They could be used to transport molecules with a poor bioavailability such as curcumin in order to improve their clinical usage. This natural polyphenol, well‐known for its antioxidant and anti‐inflammatory properties, has a poor solubility that limits its clinical potential. For this purpose, the use of NDS27, a curcumin salt complexed with hydroxypropyl‐beta‐cyclod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Another study with hepatic HuH-7 cells showed that curcumin entered within seconds into the cells and was already maximal after 5 min but only one-twentieth of the curcumin had entered the cells [ 46 , 47 ]. The good performance of our cell loading can be explained by a different cell preparation, that in our case were suspended cells rather than adherent cells used by Colin et al [ 28 ]. Moreover, we performed the loading in an aqueous buffer (HBSS buffer) rather than in the culture medium.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Another study with hepatic HuH-7 cells showed that curcumin entered within seconds into the cells and was already maximal after 5 min but only one-twentieth of the curcumin had entered the cells [ 46 , 47 ]. The good performance of our cell loading can be explained by a different cell preparation, that in our case were suspended cells rather than adherent cells used by Colin et al [ 28 ]. Moreover, we performed the loading in an aqueous buffer (HBSS buffer) rather than in the culture medium.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, the loading was rapid, and 20% loading capacity was reached after 2 min incubation at 37 °C ( Table 1 ). In a previous study, we loaded adherent mdMSCs with NDS27 or native curcumin for 2 h with 42 µM curcumin or NDS27, and the loading yield was only 2%, which corresponded to about 0.8 µM internalized curcumin [ 28 ]. Another study with hepatic HuH-7 cells showed that curcumin entered within seconds into the cells and was already maximal after 5 min but only one-twentieth of the curcumin had entered the cells [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations